Variations caused by physical training in the electrocardiographic outline of swine (Landrace X White Belgian) (Revista Española de Fisiología, 1990)
To find the effect of exercise on the ECG, the electrocardiographic outlines in a training group of 7 two-month-old pigs (Landrace X White Belgian) were analyzed, compared with a nontraining control group of similar characteristics. In training animals a resting bradycardia was observed with a corresponding increase in the duration of the RR interval, as well as a duration increase in the ventricular activation time. On the contrary, the programmed training in this experiment has not influenced the amplitude of the electrocardiographic waves and the magnitude and orientation of the cardiac vectors.